O processo de gestão ambiental em unidades de conservação da natureza: um estudo de caso no Parque Estadual Dunas de Natal - de Medeiros, Andressa Andrade; da Silva, João Gomes; Teixeira, Maria do Socorro Gondim (Revista Gestão da Produção Operações e Sistemas, 2006)
The purpose of this paper is to show the importance of the environmental management applied to theconservation units of nature, focusing on the State Duna Park in Natal, Brazil. It has as a reference a theoreticaldiscussion on the ecological management, environmental valuation and environmental management,proposing the demonstration of a brief report on the environmental externalities in the ecological managementprocess. It uses, as a methodology, the bibliographical and exploratory research and the study case. The resultspresent some measures adopted by the park in order to facilitate the management process of the enterprise,regarding the ecological issues and the principles of economic sustainability. It allows for the development,stimulation and diffusion of the aspects and practices inherent to the environmental management and theecological awareness. Lastly, this paper considers that the performed activities integrate a systemic processwhose results must be constantly followed and adjusted according to the demands caused by the evolutionprocess of the environmental management.Keywords: Environmental management; Conservation units; Duna Park.